Marketing cigarettes when all else is unavailable: evidence of discounting in price-sensitive neighbourhoods. Issue Volume 23: Issue e1(2014) (13th November 2013) - Burton, Suzan; Williams, Kelly; Fry, Rae; Chapman, Kathy; Soulos, Greg; Tang, Anita; Walsberger, Scott; Egger, Sam
Abstract : Objective: Since price is both a key determinant of smoking and one of the few remaining marketing strategies available in countries without point-of-sale tobacco display, this study examines cigarette price variations in the Australian market and assesses whether those variations are consistent with price being used to increase or maintain smoking among price-sensitive groups. Method: An audit of 1739 tobacco retailers was used to collect variations in the price of the best-selling Australian cigarette brand, as well as record retailer compliance with tobacco retailing legislation. We examined variation in pricing across outlet type, demographic variations (socioeconomic level, % in the area under 18 and % born in Australia), remoteness and retailer compliance with tobacco retailing legislation. Results: Multipacks were offered by 27.8% of retailers, with the average pack price in a twin pack 1.32 (or 7.3%) cheaper than a single pack. Prices were significantly lower in some outlet types, in lower socioeconomic postcodes and in those with a higher percentage of people under 18. In contrast with other consumer goods, prices were lower (although not significantly so) outside major cities. Conclusions: The provision of substantial multi-pack discounts and lower prices in postcodes with a higher proportion of price-sensitive smokers (young people and those from lower socioeconomic groups) is consistent with targeted discounts being used as a tobacco marketing strategy. The results support policy interventions to counter selective discounts and to require disclosure of trade-based discounts.